2019
DOI: 10.1093/sleep/zsz248
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea among Australian Aboriginal and non-Aboriginal patients in the Northern Territory of Australia—a comparative study

Abstract: Australian Aboriginal and Torres Straight Islanders (ATSI) are noted to have a higher burden of chronic health conditions. However, there is a paucity of data on obstructive sleep apnoea (OSA) in this population. In this retrospective study, we evaluated the clinical and polysomnographic (PSG) characteristics of ATSI and non-ATSI adult patients who underwent diagnostic PSG between 2011 and 2015. There were a total of 3078 patients. Of the total, 403 (13%) were of ATSI origin. Among those of ATSI origin, 61% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 32 publications
1
55
1
Order By: Relevance
“…Similar data from Central Australia and far north Queensland reported that compared with non-Indigenous people, Indigenous people diagnosed with OSA were more likely to be female, live in remote communities and be obese [54]. This is an area for further research given the prevalence of obesity in Indigenous communities and the associated risk of OSA with adverse health outcomes and increased all-cause mortality [53].…”
Section: Limitationsmentioning
confidence: 70%
See 1 more Smart Citation
“…Similar data from Central Australia and far north Queensland reported that compared with non-Indigenous people, Indigenous people diagnosed with OSA were more likely to be female, live in remote communities and be obese [54]. This is an area for further research given the prevalence of obesity in Indigenous communities and the associated risk of OSA with adverse health outcomes and increased all-cause mortality [53].…”
Section: Limitationsmentioning
confidence: 70%
“…Two reports have since added to the Australian Indigenous context. A retrospective analysis of diagnostic sleep test data from the Northern Territory found that severe sleep apnoea was associated with male gender, increasing age, higher body weight, and Indigenous status [53]. Similar data from Central Australia and far north Queensland reported that compared with non-Indigenous people, Indigenous people diagnosed with OSA were more likely to be female, live in remote communities and be obese [54].…”
Section: Limitationsmentioning
confidence: 95%
“…The study participants who self-identified as only of Australian Aboriginals aged 18 years and over from our previous study cohort 28 were included in this study. Patients who identified to be of both Aboriginal and/or Torres Strait Islander origin (ATSI) or Torres Strait Islander origin alone (TSI) were excluded from the study, in order for this study to represent a uniquely defined Australian Aboriginal cohort with similar genetic/ethnic, cultural pool, exposed to similar environmental and living conditions.…”
Section: Study Participantsmentioning
confidence: 99%
“…The sleep studies which were performed and analysed during this study period were according to the 2007 American Academy of Sleep Medicine recommendations and as described in the previous study. 28 All failed sleep studies, type 3, type 4 (limited sleep studies), continuous positive airway pressure (CPAP) initiation/titration studies, and studies in which AHI or sleep architecture was not available were excluded.…”
Section: Polysomnography (Psg)mentioning
confidence: 99%
See 1 more Smart Citation